Strategi Penggunaan Kitab “Al-Arabiyah Li Al-Nasy’in Jilid 4 “ Dalam Meningkatkan Ketrampilan Berbicara Bahasa Arab Kelas 7 MTS Ma’had Darullughah Wada’wah Bangil - Faruq Abdul Muid; Firdausi Nurharini; Luluk Akhmad Baagil (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2022)
This study aims to find out how to improve Arabic speaking skills in grade 7 MTS by using teaching materials, namely the book Al-Arabiyah Li Al-Nasyi'in volume 4. It can be concluded that improving these skills is as has been examined by researchers in the study the book that students can easily improve their Arabic speaking skills by using the book Al-Arabiyah Li Al-Nasyi'in because it contains stories, mufrodat making it easier to talk to the other person speaking as well as the inhibiting factors of the book that students find it difficult in speak Arabic because the sentences are difficult to learn. So far, the process of learning Arabic in class 7 MTS Darullughah wada'wah Bangil is in improving Arabic speaking skills with the Imla' method. So in this study, to improve the language skills of class 7 MTS teaching materials were used, namely the book Al-Arabiyah Li Al-Nasyi'in volume 4. The aims of this research are (1) to identify and describe the inhibiting factors for using Al-Arabiyah Li Al-Nasyi'in volume 4 to improve Arabic speaking skills in grade 7 MTS Darullughah wa Da'wah Bangil. (2) To find out and describe the strategy for using the book Al-Arabiyah Li Al-Nasyi'in volume 4 to improve speaking skills in grade 7 MTS Darullughah wa Da'wah Bangil. In this study the researcher used a qualitative method by using the results of interviews, documentation and observations from the results of the research which found that students used the book more easily in improving their speaking skills in Arabic because it can be learned for beginners.